Basic Science for the Clinical Gastroenterologist: A Review of the Recent Literature on the Small Bowel – Part II. (1st August 1994) - Thomson, ABR
Abstract : In small bowel science, as in all parts of medicine, there has been a recent explosion of information. This is the second of a two-part series in which the scientific basis of clinical gastroenterology practice and its future are considered. Advances in understanding the mechanisms of intestinal transport are examined, followed by a perspective of intestinal adaptation in health and disease. The author also discusses clinically important areas of motility and bloodflow.